Guest Editorial Vol6 no1 - Steven Paterson (Scottish Journal of Residential Child Care)
In the period since I took up my post at SIRCC in October 2005, I have been involved in a range of projects which have been inspirational although perhaps none more so than the development of a manifesto for children and young people in care. This manifesto, which is called No Time to Lose (Elsley, 2006), is the first in the UK which has been developed specifically to consider children and young people looked after away from home.